Successful treatment of severe quetiapine intoxication with CytoSorb hemoadsorption. (10th May 2022) - Reuchsel, Caterina; Gonnert, Falk A.
Abstract: What is known and objective: While many drug poisonings are successfully treated with specific antidotes, intoxications with tricyclic antidepressants and/or atypical neuroleptics still represent a major challenge. Besides conventional approaches, a new hemoadsorption device might represent an opportunity for therapeutic detoxification. Case summary: We report a 64‐year‐old female patient who attempted suicide by ingesting an unknown dose of quetiapine. Following application of all available standard diagnostic and therapeutic measures, she was admitted to the intensive care in a deeply somnolent state. Gastroscopy was performed necessitating analgo‐sedation, intubation, and mechanical ventilation. Since quetiapine is in principle not dialysable, CytoSorb hemoadsorption was commenced resulting in a clear and rapid decrease in plasma levels of quetiapine and its metabolite norquetiapine over the next few hours. The next day, analgesia was stopped, the patient became alert, and cooperative so that she could be extubated without issues. CytoSorb blood purification therapy was discontinued after 2 days. One day later, the patient was transferred to a psychiatric clinic. What is new and conclusion: We were able to quickly and efficiently reduce quetiapine and norquetiapine to non‐toxic serum levels and to stabilize a critical situation using CytoSorb. Therefore, in the absence of a proven beneficial treatment regimen, the use of CytoSorb might represent an alternative for life‐threatening complications of quetiapine intoxication. In particular, intoxications caused by lipophilic agents should be further evaluated. Abstract : Plasma quetiapine and norquetiapine levels during the course of Continuous Veno Venous Hemodialysis (CVVHD) + 2 hemoadsorption treatments over 40 h. Note that the pre‐adsorber inlet levels (black triangles) simultaneously represent systemic levels and therefore the overall decrease in plasma levels.